Restoring cellular copper homeostasis in Alzheimer disease: a novel peptide shuttle is internalized by an ATP-dependent endocytosis pathway involving Rab5- and Rab14-endosomes - Okafor, Michael; Champomier, Olivia; Raibaut, Laurent; Ozkan, Sebahat; El Kholti, Naima; Ory, Stéphane; Chasserot-Golaz, Sylvette; Gasman, Stéphane; Hureau, Christelle; Faller, Peter; Vitale, Nicolas (Frontiers in Molecular Biosciences, 2024)
CPPs, or Cell-Penetrating Peptides, offer invaluable utility in disease treatment due to their ability to transport various therapeutic molecules across cellular membranes. Their unique characteristics, such as biocompatibility and low immunogenicity, make them ideal candidates for delivering drugs, genes, or imaging agents directly into cells. This targeted delivery enhances treatment efficacy while minimizing systemic side effects. CPPs exhibit versatility, crossing biological barriers and reaching intracellular targets that conventional drugs struggle to access. This capability holds promise in treating a wide array of diseases, including cancer, neurodegenerative disorders, and infectious diseases, offering a potent avenue for innovative and targeted therapies, yet their precise mechanism of cell entry is far from being fully understood. In order to correct Cu dysregulation found in various pathologies such as Alzheimer disease, we have recently conceived a peptide Cu(II) shuttle, based on the αR5W4 CPP, which, when bound to Cu(II), is able to readily enter a neurosecretory cell model, and release bioavailable Cu in cells. Furthermore, this shuttle has the capacity to protect cells in culture against oxidative stress-induced damage which occurs when Cu binds to the Aβ peptide.The aim of this study was therefore to characterize the cell entry route used by this shuttle and determine in which compartment Cu is released. Pharmacological treatments, siRNA silencing and colocalization experiments with GFP-Rab fusion proteins, indicate that the shuttle is internalized by an ATP-dependent endocytosis pathway involving both Rab5 and Rab14 endosomes route and suggest an early release of Cu from the shuttle.